Retention Rate and Institutional Passing Rate in The Licensure Examination for Certified Public Accountants: A Basis for Policy Review - Goshen A. Galang; Francis Earl B. Mesa; King Eduard C. Pua; Sep Keron F. Salvador; Jerome D. Marquez; Karen Joy A. Catacutan (Research Synergy Foundation, 2024)
The retention policy serves as a key criterion for determining student suitability for a program and encourages serious engagement with their studies. By enforcing a retention policy, universities can increase the number of students who pass board examinations because students are motivated to meet standardized grading requirements. The Licensure Examination for Certified Public Accountants (LECPA) is recognized as one of the most difficult board exams in the Philippines, with passing rates that are relatively low and showing a declining trend. This trend is influenced by various factors, including retention policies, exam difficulty, and other school-related elements. Further research at regional and national levels is needed to clarify these issues. This study aimed to investigate the relationship between the retention rate and institutional passing rate in the LECPA at the University of Saint Louis-Tuguegarao (USLT), as well as to suggest potential modifications to the accountancy program’s retention policy. The research focused on graduates from the Bachelor of Science in Accountancy program at USLT for the academic years 2017–2020 and 2022. Data analysis was performed using frequency, percentage, and Pearson Correlation Coefficient methods. The findings indicate that higher retention rates correlate with higher institutional passing rates in the LECPA, suggesting that USLT should consider reviewing its retention policy.